MINE! Stop motion animation - Lai, Yao Khuan (2015)
“MINE!” is a lighthearted stop motion animation that revolves around a young boy who was brought upon an unexpected journey. In my report I will be covering what were my initial thoughts and ideas and what were the process that happened to achieve the final film. The report will also cover the underlying meaning and purpose behind each visual element, which will be accompanied by reference images.